Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Tenaga Pendidik di Madrasah Aliyah Pondok Pesantren Modern Al-Kinanah Jambi - Nuning Setia Ningsih; Kemas Imron Rosadi; Mahmud MY (Departement of Mathematics Education, 2023)
This research is about the leadership of the madrasah head in improving the quality of teaching staff at Madrasah Aliyah Pondok Pesantren Modern Al-Kinanah Jambi. Issues related to leadership are interesting to study, because we want to see the policy of the madrasa head as a leader in advancing his school regarding the quality of teaching staff. This type of research is using a qualitative approach and this research is descriptive qualitative because it has the ability to reveal the problems in this research. The results of the study found that the leadership style used by madrasa heads was democratic and situational delegation. The planning carried out by the head of the madrasa in improving the quality of teaching staff at Madrasah Aliyah Pondok Pesantren Modern Al-Kinanah Jambi is compiling a program and analyzing which program needs will be prioritized in its implementation. The head of the madrasa in the implementation of improving the quality of teaching staff at Madrasah Aliyah Pondok Pesantren Modern Al-Kinanah Jambi, namely On The Job Training in the form of training and guidance while Off the job training is in the form of Subject Teacher Workshops and Consultations (MGMP). While the supervision carried out by the head of the madrasa conducts monitoring or monitoring directly and indirectly after that the head of the madrasa gives rewards or awards and sanctions to educators who commit violations. Supporting factors: Supporting factors, namely: The Madrasah Head's dedication to his leadership responsibilities and Having educators who are young and have high enthusiasm. While the inhibiting factors are: lack of funds and problems in the development of facilities and infrastructure